1988
DOI: 10.1007/bf00174524
|View full text |Cite
|
Sign up to set email alerts
|

Apomorphine doses impair the reaction time of fast reacting but not slow reacting rats

Abstract: Previously, several studies in our laboratories have linked the ability to initiate movement rapidly (reactive capacity) in several rat strains to markers of nigrostriatal dopamine function. In the present investigation we wished to determine the extent to which fast-reacting (FR) and slow-reacting (SR) rats responded differentially to the effects of dopamine agonist (apomorphine) administration. Fisher 344 rats were operantly conditioned on a shock-avoidance, reactive capacity task which requires extremely fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The impaired SRT execution after rest confirms previous outcomes on reactivity in PD patients with exact timing of both LD intake and test performance 10. An animal study also showed an impaired RT after cued dopaminergic stimulation in a particular species of fast-reacting rats 11. Sedative effects of LD may play a role, and release of fatigue-counteracting brain norepinephrine is lower during rest than during exercise 12.…”
Section: Discussionsupporting
confidence: 80%
“…The impaired SRT execution after rest confirms previous outcomes on reactivity in PD patients with exact timing of both LD intake and test performance 10. An animal study also showed an impaired RT after cued dopaminergic stimulation in a particular species of fast-reacting rats 11. Sedative effects of LD may play a role, and release of fatigue-counteracting brain norepinephrine is lower during rest than during exercise 12.…”
Section: Discussionsupporting
confidence: 80%
“…None have reported the detrimental effect on saccadic latency we describe here, but there is evidence to suggest that in some circumstances dopamine might have an adverse effect on manual and saccadic reaction times. It has recently been reported that a simple manual reaction time task is delayed in PD patients as a result of subcutaneous apomorphine injection, a D1 and D2 receptor agonist (Muller et al 2002), and similarly apomorphine has been reported to impair the reaction time in certain strains of rats (Wilcox and Spirduso 1988). Amphetamine causes dopamine release and reuptake inhibition, and has been found to prolong saccadic latencies in humans (Dursun et al 1999), whereas haloperidol, a dopamine antagonist with mild anticholinergic action, has been found not to affect saccades (Lynch et al 1997).…”
Section: The Effect Of L-dopa On Latency Distributionsmentioning
confidence: 99%
“…To date, an impaired performance of a CRT-like paradigm after apomorphine application was only shown in a certain species of fast reacting rats (32). CRT significantly increased in our previously untreated PD patients.…”
Section: Discussionmentioning
confidence: 67%
“…We assume, that apomorphine at least partially binded to presynaptic autoreceptors and thus inhibited locomotor activity, as presynaptic dopaminergic receptors are at least six to 10 times more sensitive to dopamine agonists compared with postsynaptic dopaminergic receptors (17,32,47,48). We assume, that apomorphine at least partially binded to presynaptic autoreceptors and thus inhibited locomotor activity, as presynaptic dopaminergic receptors are at least six to 10 times more sensitive to dopamine agonists compared with postsynaptic dopaminergic receptors (17,32,47,48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation